Skip to main content

Posts

Showing posts from March, 2019

How to expand the trinomial?

How to expand the trinomial? Let we will learn to expand the square of a trinomial (a + b + c). Let (b + c) = x       Then (a + b + c) 2  = (a + x) 2  = a 2 + 2ax + x 2                          = a 2  + 2a (b + c) + (b + c) 2                            = a 2  + 2ab + 2ac + (b 2  + c 2  + 2bc)                           = a 2  + b 2  + c 2  + 2ab + 2bc + 2ca Therefore, (a + b + c) 2  = a 2  + b 2 + c 2  + 2ab + 2bc + 2ca Here are some examples only for u...... I) 2l – 3m + 4n) 2   Solution:  (2l – 3m + 4n) 2   We know, (a - b + c) 2  = a 2  + b 2  + c 2  – 2ab - 2bc + 2ca Here a = 2l, b = -3m and c = 4n (2l + (-3m) + 4n) 2 = (2l) 2  + (3m) 2  + (4n) 2  + 2 (2l) (-3m) + 2 (-3m) (4n) + 2 (4n) (2l)  = 4l 2  + 9m 2  + 16n 2  – 12lm – 24mn + 16nl Therefore, (2l – 3m + 4n) 2  = 4l 2 + 9m 2  + 16n 2  – 12lm – 24mn + 16nl (iii)  (3x – 2y – z) 2 Solution:  (3x – 2y – z) 2 We know, (a - b - c)  2  = a 2  + b 2  + c 2  – 2ab + 2bc – 2ca Here a = 3x, b = -2y and c = -z [3x + (-2y